Crystallized Ammonium Alum and Recovery of Ammonium Alum: Urea DES from Cellulose/DES Solution - Thamer Salman, Zeena; M. A. Abood, Hadi (Al-Nahrain Journal of Science, 2021)
Recycling and/or recovery of solvent are of important aim in the area of environment or cost. Deep eutectic solvents (DES’s) have been widely employed in different research or industrial area. Ammonium alum: urea DES has been researched for possible applications therefore; recovery of this DES is attempted in this paper. Ammonium alum: urea DES was separated to its constituents by crystallization of ammonium alum from a solution containing cellulose. Urea was obtained by evaporation. The crystallization occurs by adding water which breaks the hydrogen bonding of DES.Water was added in a 1.25:1 volume ratio and the resulting crystals and solid materials were examined with ATR-IR and X-Ray Diffraction.